ChemInform Abstract: An Expedient "On‐Water" Synthesis of Quinoxalines. Issue 10 (March 2015) - Samanta, Swati; Das Gupta, Arpita; Mallik, Asok K.
Abstract by reaction of various 1, 2‐diketones with 1, 2‐diamines